A arte de recriar lendas e mitos: inrtextualidade e antropofagismo - Martins, Maria Angélica Seabra Rodrigues [UNESP] (My University, 2013)
Brazilian folklore is rich in legends that inhabit in the imaginary of people and are believed to have originated among Brazilian indigenous peoples and the Africans who were enslaved by Portuguese settlers. However, when those stories are compared with the legends of the Iberian Peninsula , one can notice that a lot of elements in the Brazilian legends clearly reflect, for example, aspects of the popular narratives from Galicia and Portugal, such as “The moors” and “Yara’s legend”; “O trasno” and “Saci pererê”. The objective of this paper is to analyze those cultural traces by means of Comparative Literary and Intertextuality analysis, by observing how the context , the ruling ideology, and both social and cultural aspects retake the stories that are known to a certain culture and readapt them according to the traditions of another, thus producing new discourse-texts with local characteristics.

O folclore brasileiro é rico em estórias que povoam o imaginário popular e que se acreditava terem se originado entre os indígenas locais ou entre os africanos escravizados pelo colonizador português. Entretanto, ao se comparar tais estórias a lendas de toda a Península Ibérica, observa-se que muitos dos elementos das lendas do Brasil refletem nitidamente, por exemplo, aspectos das narrativas populares da Galícia e de Portugal, como As mouras e a Lenda da Yara, o Trasno e o Saci-Pererê. O objetivo deste trabalho é o de analisar esses traços culturais, a partir da Literatura Comparada e da Intertextualidade, observando como o contexto, a ideologia reinante, os aspectos socioculturais retomam as estórias já conhecidas por uma cultura e as adapta, segundo os hábitos de outra, produzindo um novo texto-discurso com características locais.
The art for recreating legends and myths: intertextuality and antropofagism
Keywords: Comparative literature; Intertextuality; Iberian and brazilian legends; Myth; Literatura comparada; Intertextualidade; Lendas ibéricas e lendas brasileiras; Mito